Anti–elastase, anti–tyrosinase and matrix metalloproteinase–1 inhibitory activity of earthworm extracts as potential new anti–aging agent - Azmi, Nurhazirah; Hashim, Puziah; Mat Hashim, Dzulkifly; Halimoon, Normala; Nik Ab. Majid, Nik Muhamad (Asian Pacific Journal of Tropical Biomedicine Editorial Office, 2014)
Objective: To examine whether earthworms of Eisenia fetida, Lumbricus rubellus and Eudrilus eugeniae extracts have elastase, tyrosinase and matrix metalloproteinase-1 (MMP-1) inhibitory activity. Methods: The earthworms extract was screened for elastase, tyrosinase and MMP-1 inhibitory activity and compared with the positive controls. It was also evaluated for whitening and anti-wrinkle capacity. Results: The extract showed significantly (P<0.05) good elastase and tyrosinase inhibition and excellent MMP-1 inhibition compared to N-Isobutyl-N-(4-methoxyphenylsulfonyl)-glycylhydroxamic acid. Conclusions: Earthworms extract showed effective inhibition of tyrosinase, elastase and MMP-1 activities. Therefore, this experiment further rationalizes the traditional use of this worm extracts which may be useful as an anti-wrinkle agent.